Efek Sitotoksik Dimethyl Sulfoxide (DMSO) pada sel Line MCF-7 dan HeLa - Suharyani Suharyani; Bayu Putra Danan Jaya (Politeknik Kesehatan Kemenkes Bengkulu, 2023)
Cell culture studies on drugs and natural compounds are commonly employed for early compound screening, assessing their potential therapeutic and immunomodulatory effects in vitro. Many of these compounds have limited solubility in water and are typically dissolved in lipophilic solvents. Consequently, it is crucial to employ a biocompatible and non-toxic solvent for cell viability. Dimethyl sulfoxide (DMSO) is a widely utilized solvent in in vitro testing. This study aims to investigate the effect of DMSO on the viability of HeLa and MCF-7 cell lines. The MTT method was employed to assess cytotoxic effects on the HeLa and MCF-7 cell lines. The results revealed that concentrations of 1% and 2% DMSO significantly reduced the viability of MCF-7 cells (p<0.05) compared to the control after 24 hours of incubation. Conversely, the viability of HeLa cell lines exposed to 1% and 2% DMSO concentrations did not significantly differ from the control after 24 hours. Thus, concentrations of 1% and 2% DMSO exhibited cytotoxicity towards MCF-7 cells, while no such effect was observed in HeLa cells.